Superposition Effects of Zinc Smelting Atmospheric Deposition on Soil Heavy Metal Pollution Under Geochemical Anomaly - Yu, Enjiang; Liu, Hongyan; Tu, Yu; Gu, Xiaofeng; Ran, Xiaozhui; Yu, Zhi; Wu, Pan (Frontiers in Environmental Science, 2022)
Guizhou Province is covered by a large area of carbonate rocks where, with a higher background of heavy metals under the geochemical anomaly, more than 3.6 × 105 ha of heavy metal–contaminated soil in the northwest area is related to historical indigenous zinc smelting. To explore the superposition effect of industrial source atmospheric deposition on soil, two watersheds were selected for study: 1) Maoshui reservoir watershed (MS), where there is a zinc smelting plant, and 2) Haishe lake watershed (HS), which was the control. We collected atmospheric depositions and soil for 3 years and analyzed Cadmium (Cd), lead (Pb), chromium (Cr), copper (Cu), nickel (Ni), and zinc (Zn) content. The results show that the heavy metals in the atmospheric deposition of the pollution watershed in MS were much higher than those in the control site, HS. The deposition fluxes of Cd, Pb, Cr, Ni, and Zn in MS were 27.8, 602, 145, 43.9, and 2,225 mg·m−2·a−1, respectively, and were 1.37–2.01 times higher than in HS. Soil heavy metals in MS were 1.01–5.69 times higher than in HS. The elevated concentrations were found focused from northeast to southwest around the plant but was distributed uniformly in HS. The average concentration of Cd, Pb, and Zn in the soil was 6.54, 67.4, and 264 mg·kg−1, respectively, in HS, which represents a high geochemical background even without pollution. After 13 years of deposition by prediction, the contribution of the atmospheric deposition on the soil in the zinc-smelting area was lowest, at 5.10%, for Ni, and highest, at 17.9%, for Cd. Principal component analysis of atmospheric deposition and soil heavy metals reflected that the pollution sources in MS were more diversification than those in HS. Zinc smelting atmospheric deposition showed superposition effects on the accumulation of heavy metals in soil under the geochemical anomaly in this region.